2022
DOI: 10.1007/s10919-022-00411-8
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Embracing with Daily Mood and General Life Satisfaction: An Ecological Momentary Assessment Study

Abstract: Embracing has several positive health effects, such as lowering blood pressure and decreasing infection risk. However, its association with general life satisfaction and daily mood has not been researched in detail. Here, we used a smartphone-based ecological momentary assessment (EMA) approach to monitor the daily number of embraces and daily mood in a sample of 94 adults over the course of seven days. We found that embracing frequency differed slightly over the week, with embracing occurring more frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 63 publications
3
19
1
Order By: Relevance
“…In a study that used a smart phone ecological momentary assessment (repeatedly collecting data on people's thoughts and behaviors) over seven days (N=94), hugging (embracing) was notably more frequent on weekends when it buffered against acute stress [12]. Blood pressure was decreased as well as infection risk which was related to decreased pro-inflammatory cytokines.…”
Section: Huggingmentioning
confidence: 99%
“…In a study that used a smart phone ecological momentary assessment (repeatedly collecting data on people's thoughts and behaviors) over seven days (N=94), hugging (embracing) was notably more frequent on weekends when it buffered against acute stress [12]. Blood pressure was decreased as well as infection risk which was related to decreased pro-inflammatory cytokines.…”
Section: Huggingmentioning
confidence: 99%
“…Based on this, Heatley Tejada et al concluded that lower rates of loneliness of individuals in relationships might be caused by the availability of physical contact 13 . Similarly, singles were found to receive stronger benefits to their mood than individuals in a relationship when embracing 15 . Further supporting Heatley Tejada et al’s conclusion, the amount of daily touch within one’s relationship has been found to predict well-being six months later, with the amount of touch positively associated with well-being 22 .…”
Section: Introductionmentioning
confidence: 97%
“…Subsequent completion of a brief loneliness scale revealed lower scores of neglect in those in the treatment group, which were attributed to the touch by the experimenter 13 . Supportively, daily embraces were found to reduce the negative effects of loneliness on mood 15 . Another study found that the mere sight of a leg being touched activated the same region of participants’ brains as when the person was physically touched, suggesting the sight of touch may provide similar results to actual touch 14 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Affection Exchange Theory argues that we use affective touch in favour of our survival ( Floyd et al, 2018 ). For instance, gentle touch has been found to lower anxiety, stress, depressive symptoms and improve sleep patterns ( Weze et al, 2007 ) and hugging is reported to promote a better mood and life satisfaction ( Packheiser et al, 2022 ). Affective touch is also used in treatment settings and links to improved patients’ health (e.g., reduced anxiety) and patient-therapist/carer communication ( Fleischer et al, 2009 ; Kim and Buschmann, 1999 ; Williams, 2001 ).…”
Section: Introductionmentioning
confidence: 99%